2020
DOI: 10.20965/jdr.2020.p0009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seismic Vulnerability Indices for Low-Rise Reinforced Concrete Buildings Including Data from the 6 February 2016 Taiwan Earthquake

Abstract: Communities need seismic vulnerability indices to identify which buildings are most susceptible to severe damage during earthquakes. To be of greatest value, these indices should be easy to use and should be vetted against data from previous earthquakes. To date, more than 800 reinforced concrete buildings have been surveyed after earthquakes for the purpose of evaluating a seismic vulnerability index proposed by Hassan and Sozen in 1997. This number includes 130 buildings surveyed after the 6 February 2016 ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…It should be recognized that the caveat for this exercise is that the evaluation was performed after the data were collected and processed, so there is really no prediction involved in the process. Pujol et al (2018) reviewed the different boundary lines proposed by several researchers (Hassan and Sozen 1997, Dönmez et al 2005, Ozcebe et al 2004, Gur et al 2009, Shah et al 2017) using the available data from the following earthquake events: the 1992 Erzincan earthquake, 1999 Düzce earthquake, 2003 Bingöl earthquake, 2007 Pisco earthquake, 2008 Wenchuan earthquake, 2010 Haiti earthquake, 2015 Nepal earthquake, and 2016 Tainan earthquake. It was found that the percentage of severely damaged buildings that would be deemed vulnerable is not very sensitive to the selected n value ranging from 1 to 2 and BL values ranging from 0.2% to 0.4%.…”
Section: Vulnerability Indexmentioning
confidence: 99%
“…It should be recognized that the caveat for this exercise is that the evaluation was performed after the data were collected and processed, so there is really no prediction involved in the process. Pujol et al (2018) reviewed the different boundary lines proposed by several researchers (Hassan and Sozen 1997, Dönmez et al 2005, Ozcebe et al 2004, Gur et al 2009, Shah et al 2017) using the available data from the following earthquake events: the 1992 Erzincan earthquake, 1999 Düzce earthquake, 2003 Bingöl earthquake, 2007 Pisco earthquake, 2008 Wenchuan earthquake, 2010 Haiti earthquake, 2015 Nepal earthquake, and 2016 Tainan earthquake. It was found that the percentage of severely damaged buildings that would be deemed vulnerable is not very sensitive to the selected n value ranging from 1 to 2 and BL values ranging from 0.2% to 0.4%.…”
Section: Vulnerability Indexmentioning
confidence: 99%
“…Appendix 1 refers to properties collected and studied by the writers. They follow (in format and content) from previous investigations by Shiga et al (1968), Riddell et al (1987), Hassan and Sozen (1997), Dönmez and Pujol (2005), O’Brien et al (2011), Islam et al (2018), and Pujol et al (2020). Appendix 2 lists information collected by CICM that is described at https://www.sismosmexico.org/informes.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that Eq. ( 4) needs to be calibrated for each city and the coeffi cients set in this linear inequality should change accordingly as it is discussed in the work by Pujol et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Hassan index′s simplicity has attracted attention from numerous researchers throughout the years (Liu et al, 2022;Wang et al, 2019). Many researchers that have further investigated the index by (1) adding additional structural parameters and parameters related to the seismic hazard such as the peak ground acceleration (Pujol et al, 2020), or by (2) adding weights to the CI and WI parameters to modify the classifi cation model and make the threshold more robust. Pujol et al, (2020) explains that such parameters defi ning the slope that separates vulnerable buildings are less critical than the local quality of the buildings and suggests that cities defi ne a local threshold for a retrofi t program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation